(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
ان لعبة كرة اليد من الألعاب الجماعية التي تتميز بتنوع مهاراتها الاساسية الهجومية منها والدفاعية، وخططها المتنوعة سواء كانت في الهجوم او الدفاع، والجدير بالذكر ان كل حركات الهجوم تهدف إلى الانتهاء بالتصويب على مرمى الفريق المنافس حيث تعد من أهم الواجبات المهمة في ممارسة كرة اليد وتتوقف نتيجة المباراة على دقة الأداء الفني لهذه المهارة. وهذا ما دعا الى اختيار مهارة التصويب في هذه الدراسة نظراً لأهميتها، وكونها تعتبر من المهارات الأساسية الفاعلة في هذه اللعبة. وقد تكونت عينة البحث من (12) لاعب من اللاعبين الناشئين لمركز محافظة اللاذقية، وقد تم استخدام المنهج التجريبي بأسلوب المجموعة الواحدة. وهدف البحث الى اعداد تمرينات نوعية لتطوير الدقة في مهارة التصويب من الارتكاز والتعرف على دور التمرينات في تطوير مستوى أداء مهارة التصويب والتي من الممكن ان تعطي نتائج ايجابية بعد التطبيق. حيث خضعت عينة البحث للاختبار القبلي لقياس الدقة في مهارة التصويب ومن ثم طبقت مجموعة من التمرينات النوعية التي هدفها تطوير مهارة التصويب ومن ثم القياس البعدي عند الانتهاء من تطبيق التمرينات. وبالمقارنة بين القياسين القبلي والبعدي لعينة البحث اظهرت نتائج الدراسة أن التمرينات النوعية المستخدمة في تعليم وتطوير مهارة دقة التصويب من الارتكاز ادت الى تحسن ملحوظ في مستوى عينة البحث. أوصت الدراسة الى أهمية استخدام برامج تدريبة مبنية على أسس علمية في تطوير الأداء المهاري في كرة اليد. وضرورة استخدام تمرينات هادفة ومنظمة ومراعاة الفئات العمرية والمستوى المهاري عند استخدام تمرينات لتطوير مهارة التصويب. The game of handball is a group of games characterized by a variety of basic skills offensive and defensive, and varied plans, whether in the attack or defense, it is worth mentioning that all movements of the attack aimed at finishing the correction against the opposing team, which is one of the most important duties in the practice of handball and stop The result of the match on the accuracy of the technical performance of this skill. This is what called for the selection of the skill of correction in this study because of its importance, and that it is considered a key skills players in this game. The research sample consisted of (12) young players from the center of Lattakia Governorate. The experimental method was used in a group style. The aim of the research is to prepare qualitative exercises to improve the accuracy of the skill of the correction and to identify the role of the exercises in the development of the skill level of correction, which can give positive results after application. Where the sample was subjected to tribal testing to measure accuracy in the skill of correction and then applied a set of specific exercises aimed at developing the skill of correction and then telemetry when the completion of the exercise. In comparing the tribal and remote measurements of the sample, the results of the study showed that the specific exercises used in teaching and developing the skill of accuracy of the correction of the base resulted in a significant improvement in the level of the research sample.